Synthesis of some furo-thiazolidine derivatives starting from aldimines - Öcal, N; Aydogan, F; Yolaçan, C; Turgut, Z (HETERO CORPORATION, 2003)
Alkyl and aryl substituted furothiazolidine derivatives have been synthesized by the reaction of Wittig reagent with benzylidene derivatives of 4-thiazolidinones obtained from aldimines and thioglicolic acid.
Keywords: TRANSFORMATIONS; Chemistry